2020
DOI: 10.1101/2020.02.27.20028530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypokalemia and Clinical Implications in Patients with Coronavirus Disease 2019 (COVID-19)

Abstract: medRxiv preprint BACKGROUND SARS-CoV-2 has caused a series of COVID-19 globally. SARS-CoV-2 binds angiotensin I converting enzyme 2 (ACE2) of renin-angiotensin system (RAS) and causes prevalent hypokalemia METHODSThe patients with COVID-19 were classified into severe hypokalemia, hypokalemia, and normokalemia group. The study aimed to determine the relationship between hypokalemia and clinical features, the underlying causes and clinical implications of hypokalemia. RESULTS ByFeb 15, 2020, 175 patients with CO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 13 publications
3
113
1
7
Order By: Relevance
“…Thus, the level of ACE2 membrane expression and/or tissue activity may influence onset of COVID-19 infection and thus the risk of developing more severe inflammatory tissue injuries. Likewise, in a recent retrospective study of 175 Chinese COVD-19 patients requiring hospital admission, 62% showed hypokalemia, which the authors explained by altered angiotensin II deactivation by a shift in ACE1/ACE2 balance (reduced ACE2 tissue activity under COVID-19) in favor of ACE1, thus inducing aldosterone synthesis and hypokalemia occurrence (27) (Figure 1). If this hypothesis is confirmed, mineralocorticoid receptor blockers may be able to contribute to correcting this hypokalemia.…”
Section: -Ace2 and Covid-19mentioning
confidence: 95%
“…Thus, the level of ACE2 membrane expression and/or tissue activity may influence onset of COVID-19 infection and thus the risk of developing more severe inflammatory tissue injuries. Likewise, in a recent retrospective study of 175 Chinese COVD-19 patients requiring hospital admission, 62% showed hypokalemia, which the authors explained by altered angiotensin II deactivation by a shift in ACE1/ACE2 balance (reduced ACE2 tissue activity under COVID-19) in favor of ACE1, thus inducing aldosterone synthesis and hypokalemia occurrence (27) (Figure 1). If this hypothesis is confirmed, mineralocorticoid receptor blockers may be able to contribute to correcting this hypokalemia.…”
Section: -Ace2 and Covid-19mentioning
confidence: 95%
“…Laboratory examinations included routine testing, analysis of immuno logical responses, and measurement of bio markers for monitoring lung, liver, myocardial, and renal functions. We compared the prevalence of abnormal clinical indices of the paediatric patients with previously reported data for 175 adults with COVID-19 in Wenzhou, 17 44 paediatric patients with SARS in Hong Kong, 10,18 and 167 Chinese paediatric patients with H1N1 influenza. 19…”
Section: Laboratory Tests (Reference Values)mentioning
confidence: 99%
“…in patients with underlying cardiac disorder. There is particular concern about hypokalemia in COVID-19, due to interaction of SARS-CoV-2 with renin-angiotensin-aldosterone system [7]. Hypokalemia increases vulnerability to various tachyarrhythmias.…”
Section: Pathogenic Considerationsmentioning
confidence: 99%